Multi-locus genome-wide association studies reveal the genetic architecture of Fusarium head blight resistance in durum wheat - Haile, Jemanesh K.; Sertse, Demissew; N’Diaye, Amidou; Klymiuk, Valentyna; Wiebe, Krystalee; Ruan, Yuefeng; Chawla, Harmeet S.; Henriquez, Maria-Antonia; Wang, Lipu; Kutcher, Hadley R.; Steiner, Barbara; Buerstmayr, Hermann; et al. (Frontiers in Plant Science, 2023)
Key message: This study identified QTL with significant effects associated with FHB resistance in Canadian and European durum wheat cultivars and breeding lines by performing a multi-locus genome-wide association study. Six stable QTL were identified and KASP markers were developed and evaluated in the Global Durum Panel to support marker-assisted selection.Durum wheat is more susceptible to Fusarium head blight (FHB) than other types or classes of wheat. The disease is one of the most devastating in wheat; it reduces yield and end-use quality and contaminates the grain with fungal mycotoxins such as deoxynivalenol (DON). A panel of 265 Canadian and European durum wheat cultivars as well as breeding and experimental lines were tested in artificially inoculated field environments (2019-2022, inclusive) and two greenhouses (2019 and 2020) trials. The trials were assessed for FHB severity and incidence, visual rating index, Fusarium damaged kernels, DON accumulation, anthesis or heading date, maturity date and plant height. In addition, yellow pigment and protein content were analyzed for the 2020 field season. To capture loci underlying FHB resistance and related traits, GWAS was performed using a single-locus and several multi-loci models, employing 13,504 SNPs. Thirtyone QTL significantly associated with one or more FHB-related traits were identified, of which nine were consistent across environments and associated with multiple FHB-related traits.Although many of the QTL were identified in regions previously reported to affect FHB, the QTL QFhb-3B.2, associated with FHB severity, incidence, and DON accumulation, appears to be novel.We developed KASP markers for six FHB-associated QTL that were consistently detected across multiple environments and validated them on the Global Durum Panel (GDP). An analysis of allelic diversity and frequencies of these revealed that the lines in the GDP harbor between zero to six resistance alleles. This study provides a comprehensive assessment of the genetic basis of FHB 2 resistance and DON accumulation in durum wheat. Accessions with multiple favorable alleles were identified and will be useful genetic resources to improve FHB resistance in durum breeding programs through marker-assisted recurrent selection and gene stacking.